Conduction mode: broadening the range of applications for laser welding - Assuncao, D. E.; Ganguly, Supriyo; Yapp, David; Williams, Stewart W. (Cranfield University, 2012)
Conduction laser welding opens up a range of innovative applications for laser welding. This relatively novel mode of laser processing expands the application potential significantly beyond what is normally achieved today. The main reason for this could be attributed to the different characteristics of conduction process when compared to keyhole laser welding. An example is the higher stability of conduction which results in welds of higher quality and better control of the welding process. Despite the advantages of conduction laser welding, it is yet to be exploited significantly for industrial applications and there are very few applications for which this mode of operation is used. This paper is aimed at presenting different varieties of applications for conduction laser welding using a fibre laser. This ranges from high quality aluminium welds to laser brazing of stainless steel to metal foams. The objective of this paper is to highlight the main features of conduction laser welding process and exemplify some conduction laser welding applications.